2018
DOI: 10.1016/j.cmi.2017.07.018
|View full text |Cite
|
Sign up to set email alerts
|

Maternal pneumococcal nasopharyngeal carriage and risk factors for neonatal carriage after the introduction of pneumococcal conjugate vaccines in The Gambia

Abstract: Objectives: Pneumococcal nasopharyngeal carriage occurs early in life. However, the role of vertical transmission is not well understood. The aims of this study were to describe carriage among mothers and their newborns, and to assess for risk factors for neonatal carriage. Methods: In a nested retrospective cohort study, we analysed data from the control arm of a randomized controlled trial conducted in The Gambia 2 to 3 years after introduction of pneumococcal conjugate vaccine (PCV) 13. Nasopharyngeal swabs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
15
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 45 publications
4
15
0
Order By: Relevance
“…Although the direct effect of PCV13 on circulating PCV13 VTs among vaccinated infants was observed 1 year after its introduction (CSS2) [16], 5 years later (CSS3) VTs were still circulating in infants who had received 3 doses of the vaccine. The PCV13 VT prevalence in this study (11.4%) is similar to VT carriage among Gambian newborns 2 years after routine PCV13 [27] but 2-fold higher than PCV13 VT prevalence in Greenlandic children <5 years old (5%) 3 years after PCV13 [28], Belgian children (5.4%) 5 years after PCV13 and 9 years after PCV7 [29], and Australian aboriginal children <5 years old (5.8%) 3 years after PCV13 and 10 years after PCV7 [30]. We saw a significant increase in serotype 19F after PCV13 introduction which was also among the most common VTs after PCV13 in the Belgian study [29].…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…Although the direct effect of PCV13 on circulating PCV13 VTs among vaccinated infants was observed 1 year after its introduction (CSS2) [16], 5 years later (CSS3) VTs were still circulating in infants who had received 3 doses of the vaccine. The PCV13 VT prevalence in this study (11.4%) is similar to VT carriage among Gambian newborns 2 years after routine PCV13 [27] but 2-fold higher than PCV13 VT prevalence in Greenlandic children <5 years old (5%) 3 years after PCV13 [28], Belgian children (5.4%) 5 years after PCV13 and 9 years after PCV7 [29], and Australian aboriginal children <5 years old (5.8%) 3 years after PCV13 and 10 years after PCV7 [30]. We saw a significant increase in serotype 19F after PCV13 introduction which was also among the most common VTs after PCV13 in the Belgian study [29].…”
Section: Discussionsupporting
confidence: 55%
“…In CSS3, we detected a significant increase in serotypes 21 and 23B. These were also the most prevalent serotypes in the post-PCV13 era in studies conducted in The Gambia [27], Italy, and Norway [39, 40]. Unexpectedly, among mothers the increase in NVTs exceeded the decrease in VTs, resulting in an overall increase in carriage.…”
Section: Discussionmentioning
confidence: 70%
“…However, we regarded the vaccination of children as the most important factor, although we found that household crowding and having siblings over the age of five were independent risk factors for nasopharyngeal carriage. This association has been observed in other studies [15]. If the siblings had been vaccinated with PCV7, this might not have been a risk factor for nasopharyngeal carriage, but the history of PCV7 vaccination for the siblings of infants was not collected in the current study.…”
Section: Discussionsupporting
confidence: 73%
“…By using culture for pneumococcal detection, we found that the prevalence of nasopharyngeal carriage was 21%. Generally higher levels of carriage have been reported from several other African countries, but there is also a great deal of variation between different regions [ 21 , 32 35 ].…”
Section: Discussionmentioning
confidence: 99%